Perilaku Konsumsi Gaya Hidup Mahasantri Pondok Pesantren Syekh Abdurrahman Rabah Perspektif Hadis - Badriyah, Nurul; Halida, Putri Alfia (Prodi Ilmu Hadis Fakultas Ushuluddin dan Dakwah Institut Agama Islam Negeri Madura, 2023)
Consumption is a resource that is needed by humans in their daily lives that produces satisfaction for them. However, consumption here has a main rule that is not excessive. The purpose of this research is to analyse the form of lifestyle consumption behaviour of mahasantri Sheikh Abdurrahman Islamic Boarding School. The research method used by researchers is phenomenological qualitative method with the type of field research. The research subjects were mahasantri and administrators. The data collection method in this study uses interviews, observation and documentation. The results showed that the consumption behaviour of the mahasantri of Sheikh Abdurrahman Islamic Boarding School varies according to their respective needs. So from the results of the study it was found that the lifestyle of the mahasantri was not classified as consumptive because they tended to shop according to their needs.